2021
DOI: 10.26420/austinjpublichealthepidemiol.2021.1117
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Test Strip Use and Overdose History among Individuals on Medication for Opioid Use Disorder

Abstract: Background: The number of deaths from drug overdose in the United States has more than doubled in the past decade. In particular, drug overdose deaths involving fentanyl have doubled every year since 2013. Rapid fentanyl test strips (FTS) are a useful strategy for detecting traces of fentanyl in substances and have received overwhelming support from individuals with opioid-dependence. Methods: We investigated fentanyl use, knowledge of FTS, willingness to use FTS, and overdose history among a sample of 105 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Approximately 50% of individuals who found that their substances were contaminated with fentanyl reported planning a behavior change in response to the results, including reducing the use or disposal of the substance, and this intended behavior was associated with a reduced risk of opioid overdose (Karamouzian et al, 2018). Other evidence has suggested that individuals who use opioids, specifically, are interested in fentanyl test strips and willing to utilize them, however, do not regularly use them because of availability issues (Mistler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of individuals who found that their substances were contaminated with fentanyl reported planning a behavior change in response to the results, including reducing the use or disposal of the substance, and this intended behavior was associated with a reduced risk of opioid overdose (Karamouzian et al, 2018). Other evidence has suggested that individuals who use opioids, specifically, are interested in fentanyl test strips and willing to utilize them, however, do not regularly use them because of availability issues (Mistler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%